Evaluasi Batuan Induk Minyak Bumi Berdasarkan Total Organic Carbon dan Rock Eval Pyrolysis Pada Daerah Nampu, Kecamatan Juwangi, Kabupaten Boyolali, Jawa Tengah - rizqi, al hussein flowers; Timotius Tuska, Robert; Erlandi, Muhammad (ReTII, 2025)
The research location is in Nampu Village, Juwangi District, Boyolali Regency, Central Java which is in the Kendang Zone and is included in the Pelang Formation. The method used in this study is TOC analysis to determine the percentage of organic material and REP to determine the type of organic matter that exists and to evaluate the potential of the shale rock of the study area as a parent rock. This study aims to determine the characteristics of shale bedrock in the research area and its relationship with oil and gas seepage found at the research site. The lithology found at the research site is in the form of interjaded napal/mudstone and calcarenite/grainstone at the bottom and napal/mudstone units with massive structures at the top. Based on the analysis of planktonic foraminifera fossils, the age of the rocks of the study site was N5-N7 in the lower layer, N6 in the Middle layer and N4-N6 in the upper layer. After being retracted, the age of the rocks at the research site has an Early Miocene age. The environmental facies of the deposition of the research site are in the Upper Interval of Parallel Lamination and Pellitic Interval which are characterized by the interplay of calkarenite/grainstone and napal/mudstone rocks at the bottom and napal/mudstone units at the top with a massive structure. The research location has a TOC content of 0.89% so it is categorized as having a medium (fair) organic matter richness. The results of the rock eval analysis of the surface sample have a medium (fair) category as a source rock that produces hydrocarbons, based on the comparison of the TOC and S2 diagrams, Tmax vs HI and HI vs OI samples have indications of Kerogen type III which tends to produce gases. The maturity of the parent rock sample based on the Tmax value has an immature level of maturity. Keyword : Source Rock, Geochemistry, Oil and Gas Seepage